Studi Eksplanatif Keputusan Finlandia Bergabung Menjadi Anggota Nato Dalam Teori Persepsi - Aden, Dimas Ashari Septa; Maulina, Annisa (Indo Green Journal, 2023)
Finland is a country that is active in various peace activities, namely in the field of peace such as peacekeeping, peacemaking and providing foreign aid. Since Russia annexed the Crimean Peninsula in 2014. This action has received criticism from various parts of the world, especially the European Union. This also made relations between Russia and Finland even colder and more limited due to the emergence of Finnish perceptions of Russia's annexation, so this gave birth to a policy in a spiral model in 2014. Relations between Russia and the European Union, especially Finland, were further exacerbated when Russia carried out a major invasion of Ukraine in 2022. So this gave birth to Finland's perception of the Russian invasion in which Russia did not seek security but instead became revisionist. So finally Finland decided to join as a member of NATO in the concept of deterrence.